Isolation of Mycobacterium monacense from chemoport: A rare case report and review of literature (Indian Journal of Case Reports, 2017)
We report a rare case of Mycobacterium monacense isolated from the blood of a patient with carcinoma breast with an infected chemoport. Initial blood cultures from peripheral line and port were sterile. Repeated blood cultures signaled positive which showed weakly stained gram positive bacilli on smear from both the vials. Nontuberculous Mycobacterial infection and speciation were confirmed by real time polymerase chain reaction and sequencing. Chemoport was removed and patient responded to 3 drug regimen with Rifampicin, Ethambutol and Clarithromycin therapy with no recurrence at 15 month follow-up.